Isolation and Characterization of Mauritanicain, a Serine Protease from the Latex of Euphorbia mauritanica L. - Flemmig, Martin; Domsalla, André; Rawel, Harshadrai; Melzig, Matthias F. (Planta Medica, 2017)
A protease called Mauritanicain was isolated from the latex of Euphorbia mauritanica L. (Euphorbiaceae) by combining ion exchange chromatography, ultrafiltration, and gel filtration chromatography. It has a high proteolytic activity against casein. The activity was only inhibited by specific serine protease inhibitors, classifying it to the serine protease family. An optimal degradation of the substrate casein takes place at a temperature of 55–65 °C and a pH of 5.5–6.5, and is unstable at pH < 5 and pH > 9. The protease is stable at temperatures from 20–70 °C, whereby the activity decreases drastically to less than 20 % at 75 °C. SDS-PAGE and matrix-assisted laser desorption time-of-flight analysis yielded a molecular weight of 73 kDa; possibly, it is natively present as a non-covalently linked dimer of a higher molecular mass > 132 kDa. Without heat denaturation, a breakdown in fractions of 73 kDa and 52 kDa was observed in SDS-PAGE. Only in some properties it shows a similarity to other characterized proteases in the plant family Euphorbiaceae, such that Mauritanicain can be presented as a new isolated protease.
Keywords: Euphorbia mauritanica; Euphorbiaceae; Mauritanicain; serine protease; plant protease; latex